Предмет: Алгебра,
автор: student3331
Решите пример из тригонометрии
Приложения:
Ответы
Автор ответа:
0
tg^2 a-sin^2 a-tg^2 a *sin^2 a=
=tg^2 (1-sin^2 a)-sin^2 a=
=tg^2 a *cos^2 a -sin^2 a=
=(sina/cosa)^2 *cos^2 a-sin^2 a=
=sin^ a-sin^2 a=0
=tg^2 (1-sin^2 a)-sin^2 a=
=tg^2 a *cos^2 a -sin^2 a=
=(sina/cosa)^2 *cos^2 a-sin^2 a=
=sin^ a-sin^2 a=0
Похожие вопросы
Предмет: История,
автор: tajtnurov
Предмет: Химия,
автор: milana090393min
Предмет: Информатика,
автор: umerbekovaalbina
Предмет: Алгебра,
автор: Kuktus
Предмет: Алгебра,
автор: yulley